(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The main objective of the current study was to develop ceritinib SNEDDS for the improvement of solubility, permeability and drug release. Solubility of ceritinib was studied in various oils, surfactants and co-surfactants and based on its maximum solubility an oil, surfactant and co-surfactant were chosen (captex355,tergitol and propylene glycol) and mixed in varying ratios , the ratios with no phase separation, maximum transmittance and clear in appearance were identified and used for plotting pseudo tertiary phase diagram. Fifteen SNEDDS formulations were selected from miscible regions of pseudo ternary phase diagram subjected to thermodynamic stability testing. Formulations that passed stability testing were evaluated for % transmission, drug content and in vitro drug release analysis. The final optimized formulation was analysed for particle size, Z average and zeta potential followed by FTIR and SEM analysis. Formulation F13 with maximum drug release of 98.9% in 60 minutes that is higher than 48 % of pure drug is considered the optimised formulation. The particle size, Z average and zeta potential of the ceritinib SNEDDS formulation F13 were 144 nm, 132 nm and -7.2 mV respectively. The FTIR and SEM studies do not indicate any drug excipient interaction and confirm uniform drug distribution. The formulation subjected to accelerated stability study is proved to be stable over a period of six months. The results indicate ceritinib SNEDDS formulations can be designed in order to enhance the solubility of ceritinib and thereby increase in its absorption rate and drug release.